ILO-PATRIS AS AN ALTERNATIVE INSTRUMENT TO OBSERVE THE WORKING CONDITIONS OF A SMALL FOOD-PRODUCING BUSINESS - Silalahi, Rizky Luthfian Ramadhan; Purwaningsih, Isti (J@ti Undip: Jurnal Teknik Industri, 2024)
The poor and hazardous work conditions of small businesses are prevalent, including the Indonesian small food-producing businesses. Observations have been commonly used to examine and describe the work conditions, although with some limitations. Despite the seemingly useful application, the ILO-PATRIS and its IPR calculation have not been used to observe the work conditions of Indonesian small food-producing businesses. This study aimed to demonstrate the applicability and usefulness of ILO-PATRIS, as an instrument to observe the working conditions of  Indonesian small food-producing businesses. A small business of tempe chips was purposively selected, with three respondents involved in the scoring of the ILO-PATRIS monitoring items. The results indicated relatively poor working conditions with ILO-PATRIS score of 30 out of 58. The IPR calculations led to the understanding that several aspects could be improved, such as the personal protective equipment and physical environment. This study demonstrated that the ILO-PATRIS and its IPR calculation are useful in observing the working conditions of an Indonesian small food-producing business. However, some recommendations of the use should be considered, which may be investigated in further studies.